EVALUASI PERLAKUAN AKUNTANSI TABUNGAN HAJI PADA PT. BANK RAKYAT INDONESIA (PERSERO) Tbk KANTOR CABANG SOASIO KOTA TIDORE KEPULAUAN - Nur, Santi Ali M.; Pangemanan, Sifrid S.; Gamaliel, Hendrik (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
Hajj savings is the product issued savings bank to help communities or clients wishing to the annual haj pilgrimage .This study aims to evaluation accounting treatment savings haji he would do to PT. Bank rakyat indonesia (Persero) Tbk Soasio Branch Ooffices Tidore city. The method of analysis that is the method used descriptive with a kind of qualitative research was conducted. The results of the study obtained that the mechanisms of accounting treatment (recognition, measurement and disclosure) savings over the cancellation of hajj pilgrimage before and after customers listed as a candidate hajj pilgrims in the ministry of religious affairs and also the mechanism of accounting treatment hajj over saving hajj after the cancellation of registration are already in accordance with Generally Accepted Accounting Principle. Keywords : Evaluation, Accounting Treatment, Hajj Saving